Modulation of tumor induction and progression of oncogenic K-ras-positive tumors in the presence of TGF-β1 haploinsufficiency - Pandey, Jyotsna; Umphress, Sarah M.; Kang, Yang; Angdisen, Jerry; Naumova, Alena; Mercer, Kim L.; Jacks, Tyler; Jakowlew, Sonia B. (Carcinogenesis (New York), 2007)
Oncogenic K-ras is one of the most common genetic alterations in human lung adenocarcinomas. In addition, inactivation of clusters of tumor suppressor genes is required to bring about classical characteristics of cancer including angiogenesis as a prelude to invasion and metastasis. Transforming growth factor-β (TGF-β) 1 is a tumor suppressor gene that is implicated in lung cancer progression. Although in vitro studies have shown that TGF-β1 and Ras pathways cooperate during tumorigenesis, the biology of interaction of TGF-β1 and Ras has not been studied in in vivo tumorigenesis. We hypothesized that inactivation of TGF-β1 in addition to oncogeneic activation of K-ras would lead to early initiation and faster progression to lung adenocarcinoma and invasion and metastasis. Heterozygous (HT) TGF-β1 mice were mated with latent activatable (LA) mutated K-ras mice to generate TGF-β1+/+, K-ras LA (wild-type (WT)/LA) and TGF-β1+/−, K-ras LA (HT/LA) mice. Both HT/LA and WT/LA mice developed spontaneous lung tumors, but HT/LA mice progressed to adenocarcinomas significantly earlier compared with WT/LA mice. In addition, WT/LA adenocarcinomas had significantly higher angiogenic activity compared with HT/LA adenocarcinomas. Thus, while oncogenic K-ras mutation and insensitivity to the growth regulatory effects of TGF-β1 is essential for initiation and progression of mouse lung tumors to adenocarcinoma, a full gene dosage of TGF-β1 is required for tumor-induced angiogenesis and invasive potential. This study identifies a number of genes not previously associated with lung cancer that are involved in tumor induction and progression. In addition, we provide evidence that progression to invasive angiogenic lesions requires TGF-β1 responsiveness in addition to Ras mutation.